Anthocyanins from Flower Extract of Clitoria ternatea to Attenuate Food-Borne Pathogen (Escherichia coli and Staphylococcus aureus) for Potential Application as Natural Food Preservative - Nur Asyiqin Azemi; Mansur, Sity Aishah; Mohamed Rehan, ‘Aisyah (Progress in Engineering Application and Technology, 2022)
Bunga telang or Clitoria ternatea extracts can be a promising alternatives as natural ingredient used in the food industry to help reduce the presence of resistant microorganisms. To aim of this study is to analyse anthocyanin, the bioactive compound from C. ternatea flower extract, on the growth and activity of Escherichia coli and Staphylococcus aureus respectively. Thus, the study on the potential anthocyanins content from C. ternatea flower extracts using ethanolic extraction, spectrophotometric method, and agar disk diffusion method was explored. Different extraction parameters were attempted to determine the best extraction parameters. The yield differed according to extraction methods, ranging from 2-20% yield from 100% starting material. As the intensity colors of the C. ternatea extract increase, the concentration of the extract also increases. A linear relationship was observed between the absorbance value with anthocyanin content in the extract, and the zone of inhibition observed. The higher the absorbance measured, the higher the anthocyanins content in the extract. With higher content of anthocyanins, the more susceptible the microorganism is to the antimicrobial agent, and hence the larger the zone of inhibition. From this study, small zones of inhibition were observed from dried C. ternatea extract (between 0.8-10mm zone of inhibition on E. coli growth and between 0.7-4mm zone of inhibition on S. aureus growth), due to the low anthocyanin concentration. For future works, it is recommended to increase the concentration of flower extract up to 1000 mg/mL to properly assess its antimicrobial potential. Minimum inhibitory concentration (MIC) value should also be determined. Alternatives to current extraction method should also be explored to evaluate the yield using different extraction methods and extraction efficiency.